Analisis Pengukuran, Pengakuan, dan Penyajian Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) pada Koperasi Unit Desa (KUD) ADITAMA Kecamatan Jetis Kabupaten Ponorogo - Mega Tawang Putri Purwandari (Jurnal Riset Ekonomi dan Akuntansi, 2024)
Village regulations aim to recognize and respect villages that existed before and after the founding of the Unitary State of the Republic of Indonesia, as well as clarifying the legal status and security of villages in the constitutional system of the Republic of Indonesia, realizing justice for all Indonesian people, preserving and advancing the customs, traditions and culture of the community. village, village community initiative to develop village potential and assets for shared prosperity, movement, increased participation, formation of a professional, efficient community and effective, open and responsible village government. Village regulations regulate village authority based on ancestral rights and privileges at the local village level. Implementation will be monitored by village communities and village advisory committees. This is intended so that the implementation of village regulations is always supervised by the local village community, because these village regulations are issued for the benefit of the village community (Law Number 6 of 2014).